THE EFFECT OF ECONOMIC SOCIAL CHARACTERISTICS TO THE FARMERS 'ATTITUDE IN THE IMPLEMENTATION OF SRI METHOD (SYSTEM OF RICE INTENSIFICATION) ON RICE - Khairunisa Rangkuti; Ainul Mardhiyah; Muhammad Syafii (JASc (Journal of Agribusiness Sciences), 2017)
The purpose of this research is to know the application of SRI (System of Rice Intensification) method in Pematang Setrak Village, to analyze farmer attitude toward SRI (System of Rice Intensification) method and to know the influence of socio-economic characteristics of farmers (age, education,  number of dependents  and  land area) on farmers attitude in the application of SRI (System of Rice Intensification) method. The method used is descriptive method and multiple linear analysis. From the research results obtained: 37.50% and 35%, the attitude of farmers strongly agree and agree with the implementation of this method of SRI means that rice farmers in the village of Pematang Setrak Teluk Mengkudu Sub district Serdang Berdagai district accept and give a positive attitude towards the application of SRI Method (System of Rice Intensification). From the multiple regression analysis obtained R-Square value of 0.816, it identifies that simultaneously the attitude of farmers affected by age, education, duration of farming, the number of dependents, and the land area of 81.6%, and the remaining 18.4% influenced by other factors outside variables studied. While partially tested the variables that affect the attitude of farmers are age variables, the number of dependents, and land area whereas education and duration of farming does not affect the attitude of farmers in the application of SRI method.Keyword :  Rice, SRI Method, attitude of farmer